Effects of contract farming on production and income of sunflower farmers in Kongwa district In central agricultural zone of Tanzania - Mpeta, Daniel Fabiano (Mzumbe University, 2015)
This thesis undertakes to explore the effects of farming contracts on technical efficiency of production and incomes of smallholders in Kongwa District. Of great interest in the study is fact that, farming contracts examined involve sunflower crop, a low value crop which does not belong to conventional crops considered to be ideal crops for contract farming. Most contract crops as described in Prowse (2012) are often those which exhibit higher net return per hectare of land than staples; have high degree of perishability and require product homogeneity in their production, high hygiene, and safety requirement at the end market. They are crops such as vegetables, fruits, flowers, ornamentals, condiments and spices whose transactions costs in spot market are usually high (Temu&Temu, 2005; Prowse, 2012). Sunflower does not have such characteristics. It is an easy to grow crop, an indispensable edible crop, with low perishability and with many buyers. Econometric modeling is used to determine the contract effects on productivity and income of sunflower farmers. Considering contract farming as a governance form between smallholders and agri-business firms, the study uses a value chain approach to examine the role of contracting firms in coordination of trade relationships. A cross-sectional data set of 400 small-scale sunflower farmers in Kongwa District and chain survey data covering 7 sunflower processing firms based in Dodoma and Singida practicing contract farming are used. Results show that participating in contract farming lead to an average increase in technical efficiency of a farmer by 4.5- 7.4 percent. Contract participation also increases land productivity of a farmer. The expected output per acre of contract farm is 24% higher than non-contact farm. Similarly, contract farmers realize positive income effects from sunflower production. Results also show that innovativeness of firms and collaborations with Local Government Authorities, are a key to contract farming success. Promotion of contract farming could be done by e.g. providing improved services to contract firms and farmers such as by supporting the availability of improved seeds, and creating conducive contract farming laws and regulations.